Reproductive intentions in mothers of young children with sickle cell disease. Issue 5 (17th February 2020) - Schultz, Corinna L.; Tchume‐Johnson, Trudy; Jackson, Tannoa; Enninful‐Eghan, Henrietta; Schapira, Marilyn M.; Smith‐Whitley, Kim
Abstract: Background: Sickle cell disease (SCD) is an autosomal recessive hemoglobinopathy associated with morbidity and mortality. We sought to understand family planning intentions of parents of young children with SCD including the awareness of three reproductive options (adoption, in vitro fertilization with egg/sperm donation [IVFD], in vitro fertilization [IVF] with preimplantation genetic testing [IVF/PGT]) to decrease the risk of having a child with SCD. Procedure: Qualitative, semistructured, one‐on‐one interviews with 18 female parents of young children with SCD at an urban, tertiary care pediatric hospital. Results: Half of the parents knew their hemoglobinopathy status or their partner's status before pregnancy. Eight parents chose to have no further children because of fear of SCD in another child. Awareness of reproductive options prior to study enrollment was limited. After brief introduction, 7 parents would consider adoption, 2 IVFD, and 10 IVF/PGT. Desire for a biological child, fear of parental jealousy, ethical or religious considerations, and cost affected the acceptability of these options. Participants universally wanted information about reproductive options available to others prior to pregnancy. Conclusions: There is limited awareness and variable acceptability of alternative reproductive options available to decrease the risk of a future child having SCD. Participants universally endorsed the need for education regarding hemoglobinopathy status, SCD, and reproductive options prior to pregnancy because for many participants having a child with SCD affected their reproductive intentions. Educational interventions to ensure informed reproductive decision making should be sensitive to desires for a biological child, and ethical and financial considerations.